Analysis of movie genres experiencing when changing post-production stylistic elements of the media - Kompare, Rok; Gabrijalčič Tomc, Helena (Journal of Print and Media Technology Research, 2023)
In this paper, we have analyzed the changes in four stylistic elements that are present in almost every film and their influence on movie genres experiencing. In the theoretical part a review of studies that proposed different approaches for movie genres categorisation is presented. This is followed by the definition of film genres and investigation of the possibilities of set stylistic parameters and their impact on the film form. The experimental part includes the study how the stylistic elements influence the viewer’s assessment, whether it is possible to determine the genre of the movie based on just one stylistic element and at least how many elements are necessary to determine the correct movie genre. Five movie genres that were analyzed are: action, drama, horror, comedy and science fiction, and the impact of stylistic elements as color correction, camera movement (added in post-production), visual effects and music/sound effects were studied. The observers’ experience about movie genre produced with different stylistic forms was tested with the questionnaire. The results in terms of the number of observers’ correct answers in relation with the recognition of proposed genres and influence of stylistic elements and their combination were statistically analyzed. Based on the statistical analysis it was found out that adding visual effects and music/sound can be sufficient for the correct genre determination. In addition, the research has proved that a combination of two stylistic elements, but only if at least one of them is a visual effect or music/sound, is also sufficient for the correct genre determination. The analysis of the test results revealed that more than half of the respondents correctly identified the genre if at least three parameters were included.